Nonlinear Robust Control Approach Based on Integrity - Chen Jinli; Xue Yali; Liu Xingang (Institute of Advanced Engineering and Science, 2014)
A kind of Nonlinear Robust Control (NRC) approach based on integrity for multivariable systems is presented. It uses model estimator which provides the approximate model information to compensate the non-modeled dynamics, system uncertainties, and external disturbances of a system. Firstly, the existence of NRC with integrity is examined. Then, stable regions of each NRC’s parameters are calculated, and some parameters are obtained by placing suitable closed-loop poles, for meeting the design specifications of the whole control system. The proposed method is applied to two illustrative examples from literature. Results demonstrate that NRC is feasible and robust for complicated multivariable systems. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.4926